EP118/#744 Progress in uterine cancer survival in the United States from 2004–2016: who was left behind?. (4th December 2022) - Jang, Allyson; Liao, Cheng-I; Johnson, Caitlin; Mann, Amandeep; Darcy, Kathleen; Tian, Chunqiao; Ueda, Stefanie; Kapp, Daniel; Chan, John K
Abstract : Objectives: To establish trends in uterine cancer survival rates based on histology and race in the U.S. over a 13-year period. Methods: Data for patients with uterine cancer were acquired from the National Cancer Database from 2004–2016. Demographics, clinicopathologic factors, and survival information were extracted and tested using Kaplan-Meier and Cox proportional-hazard models for each time interval. Results: Of 487, 385 women with uterine cancer, 467, 258 (95.9%) had epithelial and 17, 184 (3.5%) mesenchymal tumors. The study period was divided into three time intervals from 2004–2007, 2008–2012, and 2013–2016. The survival rate over time increased from 49.9 to 50.7 to 51.1% (p<0.001). Younger patients (<50 years old) had no improvement in survival (55.4 to 55.4 to 55.5%; p=0.9), whereas older patients had slight improvement (49.1 to 50.0 to 50.6%; p<0.001). There was a marginal clinical increase in Blacks from 41.6 to 43.1 to 44.2% (p<0.001), Whites 50.8 to 51.5 to 51.86% (p<0.001), and Hispanics from 51.0 to 52.02 to 52.86%(p<0.001); however, no change observed in Asians (52.4 to 52.3 to 52.9%; p=0.16). Furthermore, there was a lack of improvement in clear cell carcinomas (41.5 to 41.8 to 42.9%;p=0.099) and mesenchymal tumors (37.0 to 37.2 to 36.8%; p=0.27). Survival of those with serous carcinomas has the largest increase (38.6 to 40.8 to 42.6%; p<0.001). Conclusions: In this large population study, the overall survival of uterine cancer patients had improved statistically, but may not be clinically meaningful. Moreover, there was a lack of improvement among young patients, Asians, clear cell and mesenchymal tumors.